2010
DOI: 10.4103/0970-1591.60446
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal outcome of fetal hydronephrosis: Implications for prenatal counselling

Abstract: Objectives: Hydronephrosis is commonly detected during antenatal scans. There are multiple conflicting prognostic factors in the literature with no clear focus on the postnatal outcome. The aim of the study is to assess the outcome of fetal hydronephrosis, based on antenatal sonography.Materials and Methods:Based on the third trimester fetal ultrasound findings, patients were divided into group I (unilateral hydronephrosis) and group II (bilateral hydronephrosis, ureteric dilatation, bladder thickening, etc). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
(16 reference statements)
4
8
0
Order By: Relevance
“…Bilateral hydronephrosis was significantly associated with a requirement for surgical intervention, as reported by Babu et al [11]. As noted by others [4,10,11,16], the other strongly associated variable was a greater degree of severity of ANH. Interestingly, referred patients underwent surgical treatment significantly more often than those born in-hospital.…”
Section: Antenatal Hydronephrosis In Northeastern Thailandsupporting
confidence: 63%
See 3 more Smart Citations
“…Bilateral hydronephrosis was significantly associated with a requirement for surgical intervention, as reported by Babu et al [11]. As noted by others [4,10,11,16], the other strongly associated variable was a greater degree of severity of ANH. Interestingly, referred patients underwent surgical treatment significantly more often than those born in-hospital.…”
Section: Antenatal Hydronephrosis In Northeastern Thailandsupporting
confidence: 63%
“…This condition-which normally requires no further invasive investigation or treatment-is associated with a milder degree of ANH from AUS findings as in previous studies [4][5][6][7][8][9][10][11]. Additionally, the milder the first PUS is, the more likely the association with transient hydronephrosis.…”
Section: Antenatal Hydronephrosis In Northeastern Thailandsupporting
confidence: 57%
See 2 more Smart Citations
“…10 In those with APD between 15-30 mm, 3/19 required surgery and prolonged follow-up was required to arrive at the decision Oktar T et al reported that the risk of postnatal surgical treatment increased threefold in patients with an APD of 7-20 mm and a diagnosis of caliectasis (relative risk 3.0, 95% confidence interval 1.07-8.40). 11 Signorelli M et al One case from the first group, three cases from the second, and seven cases from the third and 11 cases from the fourth needed surgical treatment.…”
Section: Resultsmentioning
confidence: 99%